Corporate Crime Liability towards Environmental Law in Indonesia - Emi Puasa Handayani; Mochammad Wachid Hasyim (Indonesian Journal of Law and Economics Review, 2018)
Law Number 32 of 2009 concerning Environmental Protection and Management in addition to regulating environmental protection and management, also contains criminal provisions that can be imposed on corporation. Law regulates the existence of two types of legal subjects that can be subject to criminal sanctions, one of which are including companies or corporations as rechtpersoon. This study aims to determine the implementation of the Supreme Court Regulation Number 13 of 2016 concerning Procedures for Handling Criminal Acts by Corporations against cases of corporate crime, especially those relating to criminal acts in the environmental field. The type of research that will be conduct are normative legal research with the method of legislation approach and conceptual approach. Based on the research, the criminal responsibility doctrine used in the Law is corporate vicarious liability, individual vicarious liability and personal accountability of the perpetrator, while Supreme Court Regulation tends to Individual Vicarious Liability doctrine.